Between theory and practice of conservation of natural resources: the parcialidades of Totonicapán, Guatemala - Sánchez-Midence, Luis Arturo (2013)
The theory regarding the causal search of predatory actions of human populations on natural resources points out that issues such as poverty, formal schooling, social exclusion, population density, human capital and social capital and the no access to land and political power constitute detonating aspects to encourage and strengthen this attitude in any human group. However, groups of people clustered in “parcialidades” seem to disprove this theory, which could be explained by the conservation of their ethnic identity and prevalence of a particular and differentiated culture. This reality should motivate the emergence and strengthening of intercultural power in Guatemala. A kind of power that could made possible to incorporate traditional knowledge of indigenous peoples in the design of new strategies for environmental conservation, and in finding the real root of Guatemalan nationality.  The present article seeks to demonstrate why, in some social groups, conservation of natural resources is more related to cultural aspects than to the presence or absence of items traditionally considered in this type of analysis (education, poverty, density population, human capital, etc.).